2015
DOI: 10.1039/c5cc02706c
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective adsorption in homochiral metal–organic frameworks: the pore size influence

Abstract: Uptake experiments in thin films of isoreticular chiral MOFs of type Cu2(Dcam)2(L) with identical stereogenic centers but different pore dimensions show that the enantioselectivity is significantly influenced by the pore size. The highest selectivity was found for medium pore sizes, roughly corresponding to the extension of the chiral guest molecule, limonene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 32 publications
0
62
0
3
Order By: Relevance
“…, the diffusion coefficient. Since the SURMOF pores which are activated in argon can be considered as empty, the QCM experiments allow a straightforward quantification of the uptake amount, as demonstrated in references [34,35,36]. The ferrocene uptake is determined to be 0.11 ± 0.02 µg·cm −2 , which corresponds to roughly 3/4 ferrocene compounds per HKUST-1 unit cell.…”
Section: Resultsmentioning
confidence: 95%
“…, the diffusion coefficient. Since the SURMOF pores which are activated in argon can be considered as empty, the QCM experiments allow a straightforward quantification of the uptake amount, as demonstrated in references [34,35,36]. The ferrocene uptake is determined to be 0.11 ± 0.02 µg·cm −2 , which corresponds to roughly 3/4 ferrocene compounds per HKUST-1 unit cell.…”
Section: Resultsmentioning
confidence: 95%
“…QCM enables measuring the uptake processes with rate constants ranging over many orders of magnitude . In addition, QCM in combination with homochiral SURMOFs enables the investigation of enantioselective uptake . However, different molecules cannot be distinguished by QCM; therefore, the investigation of multi‐component uptake processes using a QCM is not possible.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al demonstrated [71] that based on both theoretical (density functional theory (DFT) calculation) and experimental (UV-vis spectroscopy/molecular uptake measurements) data such azobenzene-containing MOFs allow for the switching of azobenzene from cis to trans conformation in solid state. [70] Copyright 2015, The Royal Society of Chemistry. Mater.…”
Section: Research Activities In Smlmentioning
confidence: 99%